Heterogeneous Photocatalytic Dehydrogenative Cross‐Coupling and Addition Reaction with Metal‐Loaded Titanium Oxide Photocatalysts - Hisao Yoshida (Advanced Energy & Sustainability Research, 2025)
Heterogeneous photocatalytic reactions begin with photoexcitation, followed by simultaneous reduction and oxidation processes that generate radical intermediates. These intermediates contribute to unique product selectivity due to distinct reaction mechanisms. This article presents several heterogeneous photocatalytic reactions involving metal‐loaded titanium oxide photocatalysts for organic transformations, as elucidated by our recent studies. While their productivity has not yet reached a level sufficient for practical applications, these findings of novel photocatalytic reactions demonstrate the significant potential of heterogeneous photocatalysis. Notably, since photocatalysis utilizes photoenergy to drive chemical reactions, even endergonic reactions can be promoted under mild conditions, where the photoenergy is converted into the chemical potential of the products. Various photocatalytic reactions are introduced, including dehydrogenative cross‐coupling reactions and addition reactions, along with their underlying reaction mechanisms: radical addition‐elimination, radical–radical coupling, and radical anti‐Markovnikov addition to alkene. Additionally, the roles of the metal cocatalysts are highlighted as a crucial factor influencing these unique reaction mechanisms in heterogeneous photocatalytic organic transformations.